Indonesia’s Leadership in PUIC: A Catalyst for Collective Legislation and Economic Integration (2025-2026) - Malik, Yusuf Idrus; Muttaqin, Fakih Fadilah (Journal of Islamic World and Politics, 2025)
This study examines the strategic role of Indonesia's leadership in the Parliamentary Union of the Organization of Islamic Cooperation (PUIC) during 2025–2026 to accelerate economic integration among Muslim-majority countries. Despite the large population and shared cultural and religious ties, intra-OIC trade remains stagnant due to regulatory fragmentation and weak legislative coordination. Drawing on neofunctionalism theories, this research highlights five key agendas proposed by Indonesia: harmonizing investment regulations, synchronizing legislative priorities, enhancing transparency in strategic projects, clustering key economic sectors, and developing joint investment packages. This article employed a qualitative descriptive approach, utilizing secondary data from relevant literature on PUIC. The findings suggest that Indonesia’s leadership demonstrates how neofunctionalist spillover dynamics may apply in non-European contexts, but face institutional fragmentation challenges within the PUIC framework. Specifically, findings indicate conditional potential for transforming the PUIC into a catalyst for collective economic governance, provided that structural constraints and deep-seated policy fragmentation are effectively addressed. This condition strengthens the global economic position of the Islamic world.